Characterization of an alpha 1—-3-galactosyltransferase homologue on human chromosome 12 that is organized as a processed pseudogene. - David H. Joziasse; J H Shaper; Ethylin Wang Jabs; Nancy L. Shaper (1991)
Abstract UDP-Gal:Gal beta 1----4GlcNAc alpha 1----3-galactosyltransferase is a terminal glycosyltransferase that is widely expressed in a variety of mammalian species, with the notable exception of man, apes, and Old World monkeys. We recently reported the isolation of a bovine cDNA clone that contains the complete coding sequence for this enzyme (Joziasse, D. H., Shaper, J. H., Van den Eijnden, D. H., Van Tunen, A. J., and Shaper, N. L. (1989) J. Biol. Chem. 264, 14290-14297). Using this cDNA as a probe, we have demonstrated that, although transcripts cannot be detected in a variety of established human cell lines by Northern blot analysis, homologous sequences are present in human genomic DNA. To establish that these sequences represent a human homologue of alpha 1----3-galactosyltransferase, we have used the bovine cDNA as a probe to isolate two nonoverlapping clones (HGT-2 and HGT-10) from a human genomic DNA library. Clone HGT-2 contains a 1.5-kilobase uninterrupted linear sequence similar to bovine alpha 1----3-galactosyltransferase that is organized as a processed pseudogene. This sequence, flanked by Alu type repeats, contains a short 5'- and 3'-untranslated region and a complete recognizable coding region that is 81% similar at the nucleotide level to bovine alpha 1----3-galactosyltransferase. This putative coding region contains multiple frameshift mutations and nonsense codons in all three reading frames which precludes the synthesis of a functional enzyme. Nevertheless, after optimal alignment, translation predicts a polypeptide that is 68% similar at the amino acid level to the bovine enzyme. Based on Southern analysis and limited sequence analysis, clone HGT-10 contains coding sequences similar to the NH2-terminal region of bovine alpha 1----3-galactosyltransferase. By analysis of panels of human-rodent somatic cell hybrids we have established that the nonfunctional, processed pseudogene and the human homologue represented by HGT-10 are located on human chromosomes 12 and 9, respectively. Interestingly, a comparison of the predicted amino acid sequence of the carboxyl-terminal two-thirds of human alpha 1----3-galactosyltransferase, with the corresponding region of the human blood group A, UDP-GalNAc:[Fuc alpha 1----2]Gal beta 1----4GlcNAc alpha 1----3-GalNAc-transferase (Yamamoto, F., Marken, J., Tsuji, T., White, T., Clausen, H., and Hakomori, S. (1990a) J. Biol. Chem. 265, 1146-1151), reveals a significant similarity (39%) suggesting that these two enzymes may have arisen from the same ancestral gene as a result of gene duplication and subsequent divergence.